The spatial dynamics of neighborhood change: exploring spatial dependence in neighborhood housing value change. Issue 6 (18th August 2017) - Jun, Hee-Jung
Abstract: This study examined spatial dependence in neighborhood change between 1990 and 2010 in the largest 100 metropolitan areas in the U.S. By analyzing neighborhood housing value change, this study found that there is considerable spatial autocorrelation in neighborhood change. Neighborhoods form spatial clusters in neighborhood housing value and its change. The spatial analysis also showed that there was a persistent spatial inequality between the city and suburbs but that this spatial inequality has declined over time. Finally, this study suggests that coordinating community development efforts with surrounding neighborhoods rather than taking isolated actions can result in more successful outcomes.